ANALYSIS OF INVENTORY MANAGEMENT SYSTEM AT PHARMACY OF XYZ HOSPITAL - Faisal Nugraha, Rizky
This study examines inventory management at the XYZ Hospital Pharmacy in Bandung, with a particular focus on pharmaceuticals and medical devices. The background of this research is the significant increase in healthcare costs and the importance of an effective supply chain management to reduce unnecessary expenses. Based on monthly stock and daily sales data from October 2023 to February 2024, this study uses quantitative methods to calculate optimal inventory levels, including Economic Order Quantity (EOQ), safety stock, and reorder point (ROP). The study also applies ABC analysis and cycle counting to prioritize inventory control. The results indicate that the proposed inventory policy, especially the continuous review strategy, has the potential for significant cost savings for XYZ Hospital Pharmacy. For pharmaceutical products, achieving a 99% service level could result in savings of Rp302,697,429, which constitutes 48.17% of the average inventory level. For medical devices, the potential savings are Rp70,602,064, accounting for 48.77% of the average inventory level. The total potential savings across all products amount to Rp373,299,493. These findings highlight that the hospital currently lacks effective controls for managing disposable medical equipment inventory. Implementing robust inventory policies and procedures is essential to improve cost efficiency and optimize inventory levels within the organization.